PELEPASAN ION NIKEL DAN KROMIUM BRAKET STAINLESS STEEL YANG DIRENDAM DALAM MINUMAN BERKARBONASI - Sumule, Indri; Anindita, P. S.; Waworuntu, Olivia A. (e-GiGi, 2015)
Abstract: Stainless steel bracket is one of metal components which is used in oral cavity. Metal substance that is implied can be corroded if it is placed in corrosive media, like carbonated drink. The corrosion can be seen from the release of Ni and Cr ions which are harmful for our bodies. This study aimed to obtain the release of Ni and Cr from stainless steel bracket after being immersed in carbonated drink. This was an experimental laboratory study with a post test only control group design. Samples were tested with spectrometry uv-visible to determine the release of Ni and Cr ions. There were 8 brackets as samples, divided into 2 groups, each of 4 samples. Stainless steel brackets were immersed in non-carbonated drink saliva and carbonated-drink saliva for 312 minutes. The results showed a difference of Ni and Cr ion release of both groups, but the group of brackets immersed in carbonated drink showed a greater release than the other group. The release of Ni ions in the control group had an average of 1.556 ppm and in the treatment group of 2.624 ppm meanwhile the release of Cr ions in the control group had an average of 0.038 ppm and in the treatment group of 0.109 ppm.Keywords: stainless steel bracket, ion Ni and Cr, carbonated drinkAbstrak: Braket stainless steel merupakan salah satu komponen logam yang digunakan didalam rongga mulut. Bahan logam tersebut dapat mengalami korosi bila berada di media korosif seperti minuman berkarbonasi. Korosi dapat dilihat dari pelepasan ion Ni dan Cr yang bersifat merugikan bagi tubuh. Penelitian ini bertujuan untuk mengetahui jumlah pelepasan ion Ni dan Cr dari braket stainless steel yang direndam dalam minuman berkarbonasi. Jenis penelitian ini ialah eksperimental laboratorik dengan rancangan post test only control group. Sampel dilakukan uji dengan alat spektrofotometri uv-visible untuk mengetahui pelepasan ion Ni dan Cr. Delapan buah sampel berupa larutan dibagi menjadi dua kelompok masing-masing dengan empat buah sampel. Braket stainless steel direndam dalam saliva tanpa minuman berkarbonasi dan saliva dengan minuman berkarbonasi selama 312 menit. Hasil penelitian menunjukkan terdapat perbedaan pelepasan ion Ni dan Cr pada kedua kelompok. Pada kelompok yang direndam dengan minuman berkarbonasi terjadi pelepasan ion Ni dan Cr lebih besar dengan rerata pelepasan ion Ni pada kelompok kontrol 1,556 ppm dan pada kelompok perlakuan 2,624 ppm, sedangkan rerata pelepasan ion Cr pada kelompok kontrol 0,038 ppm dan pada kelompok perlakuan 0,109 ppm. Kata kunci: braket stainless steel, ion Ni dan Cr, minuman berkarbonasi